The desirable qualities of future doctors – A study of medical student perceptions. (July 2013) - Hurwitz, Steven; Kelly, Brian; Powis, David; Smyth, Robyn; Lewin, Terry
<x xml:space="preserve">Abstract</x> Background: There is a lack of consensus regarding the qualities possessed by the ideal doctor, and very limited research regarding the views of medical students on these qualities. Aims: To investigate the views of commencing medical students regarding the desirable qualities of doctors. Methods: A survey containing a set of proposed desirable qualities of doctors identified from the existing literature was completed by 158 first-year medical students. Results: The survey had a 75% response rate. Students rated the individual qualities of empathy, motivation to be a doctor, good verbal communication, ethically sound, integrity and honesty as the most important. A factor analysis identified six categories of qualities: methodical processing, cognitive capacity, people skills, generic work ethic, role certainty and warmth. Significant differences in factor scores were found across subgroups of students (international and domestic students, with and without prior tertiary studies) on the following factors: methodical processing, which was scored highest by domestic students with prior tertiary studies, cognitive capacity, which was scored highest by domestic students without prior tertiary studies and generic work ethic, which was scored highest by international students. Conclusions: Medical students identified a range of desirable personal qualities of a doctor which varied according to student characteristics, including their prior educational experience. Future research aiming to define such desirable qualities should include a broader range of stakeholders, including students at different training levels and institutions.